Long-term changes in blood counts after intraoperative radiotherapy for breast cancer—single center experience and review of the literature - Wersal, Cornelia; Keller, Anke; Weiss, Christel; Giordano, Frank A.; Abo-Madyan, Yasser; Tuschy, Benjamin; Sütterlin, Marc; Wenz, Frederik; Sperk, Elena (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Intraoperative radiotherapy (IORT) for breast cancer is used as an upfront boost or as accelerated partial breast irradiation (APBI). To date, no description of blood count changes after IORT are available. Our analysis shows blood count changes in breast cancer patients up to 5 years after IORT ± whole breast radiotherapy (WBRT). Methods: IORT was given as APBI in 58 patients (IORT/APBI-group) and as a boost in 198 patients (IORT/WBRT-group). A median dose of 20 Gy was given intraoperatively with low energy X-rays [INTRABEAM (TM) System] and additionally 46 Gy/2 Gy per fraction to the whole breast, if WBRT was added. Blood counts were collected preoperatively, after 90 days and through year 1–5 of follow-up. Dunnett’s tests were used to calculate changes in blood counts over time. Additionally, platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR) and derived neutrophil-to-lymphocyte ratio (dNLR) were calculated for each time point. Results: Significantly decreases in the IORT/WBRT-group were seen for erythrocytes, hemoglobin, platelets and leucocytes and an increase for lymphocytes for the total follow-up period. In the IORT/APBI-group significantly decreases were seen for erythrocytes and hemoglobin for the total follow-up period. Regarding changes during follow-up compared to the preoperative value, much more significant changes were seen in the IORT/WBRT-group compared to IORT/APBI-group without any relevant impact of chemotherapy. Regarding PLR-, NLR- and dNLR-values the rate of patients over the range improved over time in both groups. Conclusions: IORT/APBI seems to have a smaller effect on blood counts compared to IORT/WBRT. Furthermore, PLR-, NLR- and dNLR-values improved over time, suggesting a positive effect on outcome after IORT in general.